Esthesioneuroblastoma as a cause of syndrome of inappropriate antidiuretic hormone. Issue 1 (31st December 2022) - Zhang, Wynne Q.; Glaun, Mica D.; Jalali, Ali; Samson, Susan L.; Gallagher, K. Kelly
Abstract: Esthesioneuroblastoma (ENB) is a rare neuroendocrine malignancy of the olfactory epithelium that infrequently presents with syndrome of inappropriate antidiuretic hormone (SIADH). We discuss the case of a 37-year-old woman with history of primary hypothyroidism and systemic lupus erythematosus (SLE) presenting with SIADH prior to the diagnosis of a left nasal cavity ENB (Kadish stage B, Hyams grade 1). Her SIADH diagnosis was obfuscated by concomitant discovery of a pituitary microadenoma, primary hypothyroidism, and adrenal insufficiency due to longstanding corticosteroid use for SLE. The ENB was discovered in the setting of recurrent epistaxis. The patient experienced resolution of her hyponatremia immediately following endonasal endoscopic tumor resection with negative margins. Workup for SIADH of unknown origin should include attention to sinus disease with MRI brain for the rare possibility of ENB. In patients with ENB with associated SIADH, repeat sodium levels may provide additional surveillance for recurrence.